Financial inclusion, Pradhan Mantri Jan Dhan Yojna Scheme and economic growth: Evidence from Indian States. (3rd June 2021) - Singh, Bhanu Pratap; Kumari, Annu; Sharma, Tanya; Malhotra, Abhishek
Abstract: The study examines the impact of financial inclusion, promoted through the Pradhan Mantri Jan Dhan Yojna (PMJDY) scheme, on the economic performance across the Indian states. Using the index of financial inclusion developed in Sarma (2008), the current study develops a three‐dimensional financial inclusion index for 25 major Indian states from 2011 to 2016 to assess the status of financial inclusion across Indian states. The impact of financial inclusion promoted through the PMJDY scheme on the economic performance of the Indian states is investigated using bootstrap corrected fixed effects estimation and inference in the dynamic panel. The study's finding suggests that most Indian states fall under the low or medium level of financial inclusion. The dynamic panel results reveal a positive and significant association between financial inclusion and economic growth across Indian states. Further, results show PMJDY scheme marginally improved the pace of economic growth but failed to improve the overall economic prosperity level across states. Poor usage of financial services and a rise in the number of dormant accounts after the PMJDY scheme's launch are the significant limitations of the PMJDY scheme's failure.